Intra‐abdominal Hypertension: An Important Consideration for Diuretic Resistance in Acute Decompensated Heart Failure. Issue 1 (20th December 2015) - Nguyen, Vinh Q.; Gadiraju, Taraka V.; Patel, Hiren; Park, Minnsun; Le Jemtel, Thierry H.; Jaiswal, Abhishek
ABSTRACT: Fluid accumulation is the hallmark of heart failure decompensation. Fluid overload and congestion are associated with recurrent hospitalizations, poor quality of life, and increased mortality in heart failure. Despite the use of high‐dose intravenous loop diuretic therapy, acutely decompensated heart failure patients may develop diuretic resistance. Diuretic refractoriness can be a result of elevated intra‐abdominal pressure (IAP) in acutely decompensated heart failure. Increased renal venous and interstitial pressures in patients with elevated IAP may lead to renal impairment and diuretic resistance. Routine approaches such as sequential nephron blockade with a combination of loop and thiazide or thiazide‐like diuretics, continuous diuretic infusion, and ultrafiltration may not be sufficient. Presented here is a case illustrating the importance of recognizing intra‐abdominal hypertension in patients with diuretic resistance. Lowering IAP improves renal perfusion, renal filtration, and diuresis. When elevated, IAP is an easily reversible cause of diuretic resistance. Additionally, abdominal perfusion pressure can be used to guide therapy to reverse end‐organ damage and avoid permanent renal replacement therapy.